Ethan Frome - Wharton, Edith, 1862-1937. (Wordsworth Editions Limited Hertfordshire, 2000)
In nineteenth-century Starkfield, Massachusetts, a poor young farmer falls in love with the vivacious Mattie, cousin of his sickly, demanding wife, and starts a devastating chain of events. Includes explanatory notes throughout the text, an introduction discussing the author and the background of the story, and a study guide.
Faculty
Keywords: Triangles (Interpersonal relations) -- Fiction; Accident victims -- Fiction; Married people -- Fiction; Rural poor -- Fiction; Family life -- Massachusetts -- Fiction; Marriage -- Fiction; Poverty -- Fiction; Farm life -- Massachusetts -- Fiction; Massachusetts -- Fiction; New England -- Fiction; Berkshire Hills (Mass.) -- Fiction; Domestic fiction